(untitled) - Combs, Kenneth; Kenneth Combs (Mason, OH)
The TEXAS REAL ESTATE EXAM PREP SMART GUIDE is the smart way to pass the Texas real estate exam with confidence! Maximize exam prep time with this all-in-one state-specific real estate exam prep guide that delivers the most exam practice available -- in one package. With hundreds of exam-style questions, answers, and rationale, you will quickly learn the best way to pass the real estate exam. The free CD-ROM includes even more national and state real-estate license exam questions, answers, and explanations. Plus, it contains a real estate math review and glossary for complete exam preparation.
Keywords: Real estate business; Real estate business; Real property